ANALISIS STATIC STRESS BEARING PADA TURBIN ALIRAN PIPA MENGGUNAKAN SIMULASI FUSION 360 - Daniel Joachim; Silvester Lam; Sobron Lubis (POROS, 2021)
Sewer pipe water turbines are made with the aim of helping the development of new renewable energy in Indonesia. Pipe water turbines utilize unused liquid waste and convert it into electricity. In this turbine certainly has a shaft, where the shaft certainly requires bearings / bearings. Bearing is one of the components that play a role in keeping the engine shaft to keep rotating on its axis and other components on its path. An example of bearing use is in turbines. The purpose of this study is to determine the calculation of stress in bearings caused by static loads or forces exerted slowly on bearings on pipe water turbine shaft. The static load used is 30 N with AISI 304 bearing material. From the results of static stress analysis simulation obtained the maximum voltage bearing results in withstanding static loads on pipe flow water turbines.